Selective Photothermolysis of Sebaceous Follicles with Gold Particles Rapidly Reduces Acne Lesions - Rizzo, Toni (MD Conference Express, 2014)
Acne occurs with large overactive sebaceous glands as a result of excessive sebum production, abnormal desquamation of follicular epithelium, and proliferation of Propionibacterium acnes, which may block the gland opening and cause inflammation. Photothermolysis of the sebaceous gland targets these contributors of acne. This article presents the results of 2 studies evaluating a novel approach to the photothermolysis of acne lesions via the delivery of gold microparticles into the sebaceous follicle.